Influence of the implementation of a multidisciplinary consultation program on adherence to the first ever course of oral antineoplastic treatment in patients with cancer. (October 2022) - Feral, Aurelie; Boone, Mathieu; Lucas, Virginie; Bihan, Céline; Belhout, Mohamed; Chauffert, Bruno; Lenglet, Aurelie
Purpose: To evaluate adherence (as measured by the medication possession ratio) to the first ever course of oral antineoplasic treatment in cancer patients before and after the implementation of a multidisciplinary consultation program (involving an oncologist, a pharmacist, and a nurse) and to investigate the program's impact on adverse events and drug-related problems. Patients and Methods: In a retrospective single-center study, we compared the medication possession ratio 2 months after treatment initiation in a control group (before multidisciplinary consultation program implementation) versus an interventional group (after multidisciplinary consultation program implementation). Results: Two months after oral antineoplasic treatment initiation, the mean ± standard deviation medication possession ratio did not differ significantly when comparing the interventional (multidisciplinary consultation program) group ( n = 33; 0.99 ± 0.06) with the control group ( n = 64; 0.94 ± 0.16) ( p = 0.062). Patients in the multidisciplinary consultation program group had fewer adverse events in general (41, vs 109 in the control group; p = 0.048) and digestive adverse events in particular (6 vs 29, respectively; p = 0.007). A total of 53 and 40 drug-related problems were identified in the control and multidisciplinary consultation program groups, respectively ( p = 0.074). Conclusions: Implementation of an multidisciplinary consultation program was not associated with a significant difference in drug adherence (as assessed by the medication possession ratio), which was good before and after implementation. The multidisciplinary consultation program was associated with a lower incidence of adverse events.